2018
DOI: 10.1080/03601234.2018.1439336
|View full text |Cite
|
Sign up to set email alerts
|

Pyrethroid residue dynamics in insects depends on the circadian clock

Abstract: Many factors may affect pesticide effectiveness against pests. One of the factors that should be considered is circadian rhythmicity. In this study, we evaluated daily variations in pyrethroid susceptibility in the house cricket, Acheta domesticus L. Crickets were exposed to a standard dose of ß-cyfluthrin at different times of a day, and pesticide residue levels were evaluated using gas chromatography. Results demonstrate that the time of pyrethroid disappearance is correlated with the circadian clock, with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…A previous study has shown that the pesticide pyrethroid in the house cricket Acheta domesticus exhibits the highest rate of decomposition at night. In line with this, house crickets maintain the highest resistance to insecticides at night (Maliszewska, Piechowicz, Maciąga, Zaręba, & Marcinkowska, 2018). Studies of intraday variation in traits further our understanding of insect physiology and provide a basis for improving pest management.…”
Section: Discussionmentioning
confidence: 93%
“…A previous study has shown that the pesticide pyrethroid in the house cricket Acheta domesticus exhibits the highest rate of decomposition at night. In line with this, house crickets maintain the highest resistance to insecticides at night (Maliszewska, Piechowicz, Maciąga, Zaręba, & Marcinkowska, 2018). Studies of intraday variation in traits further our understanding of insect physiology and provide a basis for improving pest management.…”
Section: Discussionmentioning
confidence: 93%
“…As we showed for S. littoralis , B. mori also had the lowest susceptibility to these insecticides in the second half of the night, and the highest during the day. Crickets, Acheta domesticus , also showed the highest resistance to the pyrethroid ß-cyfluthrin at night, expressed as a high survival rate [ 66 ]. The scope of research mentioned above was significantly expanded when the presented results also concerned the analysis of specific gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Hundreds of animal and human research studies corroborate the CTS mediates the responses to and consequences of a wide variety of toxic challenges. Investigations involving other species, such as insects, fish, and plants, also document prominent disparity in vulnerability according to the circadian time of exposure to insecticides and pesticides—β-cyfluthrin, chlorfenapyr, dichlorodiphenyltrichloroethane, dursban, malathion, permethrin, and trichlorfon—and herbicides—glyphosate, glufosinate, fomesafen, and chlorimuron ethyl24, 57,58,59,60,61,62,63,64,65 ) —thus demonstrating the ubiquity across species of the phenomenon of chronotoxicity.…”
Section: Chronotoxicologymentioning
confidence: 99%